Biohydrogen production from food industry waste by suspended and immobilized thermophylic bacteria - De Sousa Mendes, Jocélia <1983> (Alma Mater Studiorum - Università di Bologna, 2013)
This work describes hydrogen production by anaerobic digestion of glucose, molasses and milk whey by 4 thermophilic Thermotoga strains. In the attached-cell tests, the biofilm support characterized by the highest specific surface resulted in the best H2 rate. All the Thermotoga strains examined (T. neapolitana, T. maritima, T. naphtophila, T. petrophila) could produce H2 from glucose, molasses and milk whey, both in suspended- and attached-cell tests. With all the three substrates, the best performances were obtained with T. neapolitana. Some tests were conducted out to select the optimal carrier for the attached-cell conditions. 4 types of carrier were tested: 3 sintered glass carriers and a ceramic one; the chosen carrier was Biomax. === Questo lavoro descrive la produzione di idrogeno per digestione anaerobica di siero di latte, glucosio e melasso utilizzando 4 ceppi Thermotoga termofili. Tutte i 4 ceppi di Thermotoga testati (T. neapolitana, T. maritima, T. naphtophila, T. petrophila) sono stati in grado di produrre H2 dal siero di latte, glucosio e melasso, sia in prove con biomassa sospese che adesa. Con tutti i tre substrati, le migliori prestazioni sono state ottenute con T. neapolitana. Sono state condotte alcuni test per selezionare il supporto ottimale per le condizioni con biomassa adesa. Sono stati testati 4 tipi di supporti, 3 in vetro sinterizzato e uno in materiale ceramico; il supporto scelto è stato Biomax.